2014
DOI: 10.1111/jori.12022
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Investing in Enterprise Risk Management

Abstract: Prior studies show that enterprise risk management improves firm performance. This article investigates which aspects of enterprise risk management add value. We find that the use of economic capital models and dedicated risk managers improve operating performance. Requiring the dedicated risk manager report to the board of directors or to the chief executive officer (CEO) also increases value. The following combination of enterprise risk management initiatives yields the greatest increase in firm value: a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(149 citation statements)
references
References 67 publications
3
134
1
Order By: Relevance
“…Quon, Zeghal, and Maingot (2012) measured ERM adoption by the level of risk assessment reported in annual reports and financial statements and did not find an effect on performance. The result of a study by Grace et al (2014) shows that firms that put more emphasis on a combination of ERM-related activities (including weight on a simple economic capital model, having a dedicated risk manager or risk management team, and risk managers reporting to the board) reaped the benefits of an improved cost and revenue efficiency. The authors also found that moving from simple risk-based capital allocation models to more advanced models -based on scenarios, stress test, and stochastic simulation -did not contribute to any further performance efficiency improvements.…”
Section: A Current Stance On the Enterprise Risk Management Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Quon, Zeghal, and Maingot (2012) measured ERM adoption by the level of risk assessment reported in annual reports and financial statements and did not find an effect on performance. The result of a study by Grace et al (2014) shows that firms that put more emphasis on a combination of ERM-related activities (including weight on a simple economic capital model, having a dedicated risk manager or risk management team, and risk managers reporting to the board) reaped the benefits of an improved cost and revenue efficiency. The authors also found that moving from simple risk-based capital allocation models to more advanced models -based on scenarios, stress test, and stochastic simulation -did not contribute to any further performance efficiency improvements.…”
Section: A Current Stance On the Enterprise Risk Management Literaturementioning
confidence: 99%
“…By developing ERM into a core competence, firms can experience an increased capital efficiency in that ERM enhances a firm's ability to allocate corporate resources on an informed risk-reward trade off basis (Grace et al, 2014;. That is, firms choose between firm-specific investments by assessing the return on the investments after compensating for the costs associated with the increase in the total risk of the firm .…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Study [20] suggested that firms demonstrated progressively higher value as the ERM matured. Further, study [21] suggested that the use of a dedicated risk manager is capable of improving the firm's operating performance and emphasized that the existence of a direct reporting line from the risk manager to the board or CEO could lead to superior firm value.…”
Section: "+ ) +) ) -"mentioning
confidence: 99%
“…As the ERM is mandated for all listed companies in Malaysia, for the purpose of developing a comprehensive panoply of ERM tools, large firms may utilize greater financial resources than a small firm [27,[31][32][33]. Total revenue was used as proxy for firm size.…”
Section: /('+! * * -$'(% And+mentioning
confidence: 99%